The Milky Way: paediatric milk-based dispersible tablets prepared by direct compression – a proof-of-concept study. (28th June 2016) - Orubu, Samuel E F; Hobson, Nicholas J; Basit, Abdul W; Tuleu, Catherine
Abstract: Objectives: Dispersible tablets are proposed by the World Health Organization as the preferred paediatric formulation. It was hypothesised that tablets made from a powdered milk-base that disperse in water to form suspensions resembling milk might be a useful platform to improve acceptability in children. Methods: Milk-based dispersible tablets containing various types of powdered milk and infant formulae were formulated. The influence of milk type and content on placebo tablet properties was investigated using a design-of-experiments approach. Responses measured included friability, crushing strength and disintegration time. Additionally, the influence of compression force on the tablet properties of a model formulation was studied by compaction simulation. Key findings: Disintegration times increased as milk content increased. Compaction simulation studies showed that compression force influenced disintegration time. These results suggest that the milk content, rather than type, and compression force were the most important determinants of disintegration. Conclusion: Up to 30% milk could be incorporated to produce 200 mg 10-mm flat-faced placebo tablets by direct compression disintegrating within 3 min in 5–10 ml of water, which is a realistic administration volume in children. The platform could accommodate 30% of a model active pharmaceutical ingredient (caffeine citrate).